Assessment of Level of Knowledge, Awareness toward “Basic Life Support” and “Cardiopulmonary Resuscitation” among Dental Students, Interns, and Dental Practitioners’’ - Lovely Kumari; Archana Sudheer; Naazia Shareef; Lipi Singh; Babita; Prasanta Majumder; Miral Mehta; Shobhit Saxena (Journal of Pharmacy and Bioallied Sciences)
Background: Dentists forms an essential part of being a health care provider. It is necessary that they are adequately aware, trained, and knowledgeable about all aspects of managing an emergency condition, especially the practical aspects of basic life support (BLS) and cardiopulmonary resuscitation (CPR). Aims: The purpose of this study was to analyze dental interns and third- and final-year students in Patna, India, regarding their knowledge and attitudes about basic life support (BLS). Conclusion: The study effectively demonstrates the critical role of professional year progression in shaping BLS knowledge.